'Mayihlome!': Towards an understanding of Amalaita gangs in Durban, c.1900-1930 - La Hausse, Paul (My University, 1987)
In January 1915 eleven African youths armed with sticks were responsible for an apparently unprovoked assault on two African men. Half their number ware subsequently arrested and charged with breach of the peace. In the hot, dusty courtroom two intriguing facts came to light. Firstly, the victims of the assault were members of another more formally constituted body – the much resented African section of the Durban Borough Police. And secondly, the gang members failed to recognize them as policemen since one of them had been playing a mouth-organ. Perhaps the keen imagination of one of the youthful accused was responsible for providing the court with the vision of a policeman playing a mouth-organ, the possession of which sealed off what one official called the 'name universe' of the 'turbulent umfaan' from the ragged respectability of older African workers in the town. Either way, the ranks of youthful accused received sentences which, between 1900 and 1930, were shared by thousands of other young male workers - several months hard labour and at least ten lashes.
African Studies Seminar series. Paper presented April, 1987
Keywords: Gangs. South Africa. Durban. History. 20th century; Industrial relations. South Africa. Durban. History. 20th century; Labor. South Africa. Durban; Crime. South Africa. Durban; Youth, Black. South Africa. Durban; Durban (South Africa). Economic conditions; Durban (South Africa). Race relations